Analysis of Service Quality Improvement Strategies for the PTSP Online System using E-SERVQUAL and Importance–Performance Analysis (IPA) - Eko Ariyanto; Eri Zuliarso (SISTEMASI, 2026)
The digital transformation of higher education has increased the demand for high-quality, efficient, and user-centered electronic services. Sunan Kudus State Islamic University has implemented the Online One-Stop Integrated Service (PTSP Online) system to support academic and administrative service delivery. However, a comprehensive evaluation of its service quality from the users' perspective has not yet been conducted. This study aims to evaluate the service quality of PTSP Online, identify the gaps between users' expectations and perceptions, and determine service improvement priorities as a basis for developing strategies to enhance digital service quality. A quantitative research approach was employed using the E-SERVQUAL and Importance–Performance Analysis (IPA) methods. Data were collected through a questionnaire survey involving 382 users who had previously accessed PTSP Online for academic services. The E-SERVQUAL analysis was conducted to measure the service quality gaps between users' perceptions and expectations across five dimensions: Efficiency, System Availability and Reliability, Responsiveness, Privacy Security Assurance, and Contact and Ease of Use. Subsequently, Importance–Performance Analysis (IPA) was applied to map service attributes according to their perceived importance and performance. The results indicate that the overall service quality of PTSP Online is satisfactory, with relatively small gap values across all dimensions. The Responsiveness dimension exhibited the highest positive gap (0.06), whereas Efficiency recorded the largest negative gap (−0.03). The IPA results identified service data and information accuracy (SAR4) as the highest priority for improvement, while nine service attributes were positioned in Quadrant II (Keep Up the Good Work). This study extends the application of the integrated E-SERVQUAL and IPA approach to the context of digital administrative services in Islamic higher education institutions, an area that remains underexplored in the existing literature. Furthermore, the findings provide empirical evidence to support PTSP Online administrators in formulating sustainable strategies for improving digital service quality.